1994
DOI: 10.1002/cne.903390106
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord and trigeminal projections to the pontine parabrachial region in the rat as demonstrated with Phaseolus vulgaris leucoagglutinin

Abstract: In order to determine the regions within the parabrachial nucleus that receive synaptic input from nociceptive regions of the spinal cord and medulla in the rat, we analyzed the "Golgi-like" labeling produced by anterograde transport of Phaseolus vulgaris leucoagglutinin (PHA-L) from discrete iontophoretic injections confined to either the superficial dorsal horn of the lumbar spinal cord or to the superficial dorsal horn of the trigeminal nucleus at the level of the obex. Labeled fibers from both the spinal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
120
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 44 publications
17
120
0
1
Order By: Relevance
“…Nociceptive afferents that terminate in lPB and KF are known to ascend to dl-pons along the vsc (Slugg and Light, 1994;Bourgeais et al, 2003). In the present study, we found that many type II dendrites extended laterally into vsc, in which the distal dendritic processes also exhibited considerably higher number of varicosities.…”
Section: Pneumotaxic Neurons Integrate Pain And/or Musculoskeletal Insupporting
confidence: 61%
See 1 more Smart Citation
“…Nociceptive afferents that terminate in lPB and KF are known to ascend to dl-pons along the vsc (Slugg and Light, 1994;Bourgeais et al, 2003). In the present study, we found that many type II dendrites extended laterally into vsc, in which the distal dendritic processes also exhibited considerably higher number of varicosities.…”
Section: Pneumotaxic Neurons Integrate Pain And/or Musculoskeletal Insupporting
confidence: 61%
“…The somata and/or dendritic domains of some pneumotaxic neurons we identified were located in the lPB and KF nuclei, which are the terminating fields of some nociceptive afferents (Slugg and Light, 1994;Bourgeais et al, 2003). Recently, it was reported that certain respiratory rhythmic neurons in KF responded to cutaneous noxious stimuli and that the resulting respiratory enhancement was attenuated by bilateral inhibition of the parabrachial complex (Jiang et al, 2004).…”
Section: Pneumotaxic Neurons Integrate Pain And/or Musculoskeletal Inmentioning
confidence: 98%
“…Electrophysiological investigations and correlated anatomical data have also provided evidence that VBSNC neurons, including nociceptive neurons in subnuclei caudalis and interpolaris, contribute to VBSNC projections to the other regions noted above that are involved in pain, including its reflex expression or its modulation. These include direct projections from the nociceptive neurons to peri-aqueductal gray and the parabrachial area (from where there are projections to amygdala and hypothalamus) as well as projections to other components of the ipsilateral VBSNC, the V motor nucleus and contralateral VBSNC (lacquin et al, 1990;Hayashi, 1992;Slugg and Light, 1994;Bester et al, 1995;Jasmin et al, 1997;Meng et al, 1997;Allen and Pronych, 1997;and see Dubner and Bennett, 1983;Dubner, 1985;Sessle, 1987;Craig and Dostrovsky, 1997 As noted above, studies in either anesthetized or unanesthetized animals have documented neuronal responses to cutaneous nociceptive afferent inputs that have provided strong evidence that both NS and WDR neurons exist within the VBSNC, particularly in the subnucleus caudalis, and that they are critical brainstem elements for the detection and discrimination of superficial pain in the craniofacial region. Can a similar conclusion be applied to other forms of craniofacial nociceptive inputs?…”
Section: Other Evidencementioning
confidence: 99%
“…The lateral part of the pPB receives nociceptive information from where it is conveyed to other brain areas including the extended amygdala [40,41]. The pPB is divided into a number of subregions that project to different parts of the amygdala.…”
Section: Spinopontoamygdaloid Pathwaymentioning
confidence: 99%